Comparative Analysis of The Representation of Trump’s Jerusalem Move Issue in News Articles Of The New York Times And Al-Jazeera - Atika Yunia Rahayu; Hamzah Hamzah; Leni Marlina (English Language and Literature, 2018)
Although there have been many studies show that different news media can represent the same issue with different representations, there are very few studies that examine representations of social issues related to institutions and conflicts between countries. This study aims to, 1) explain the representation of social issues, namely Trump's Jerusalem move in news articles from The New York Times and Al-Jazeera, 2) identify the similarities and differences in the content of the news coverage on both media, and 3) analyse the bias of the media in representing the issue. The analysis in this study is based on Faiclough's (1995) theory of critical discourse analysis. To answer all questions, this theory is also elaborated with News Schemata's theory of Van Dijk (1986) and the analytical tools of text analysis from Richardson (2007). The results showed that The New York Times and Al-Jazeera represented the issue in a different way. Al-Jazeera seeks to display negative representations of Trump's Jerusalem move, while The New York Times does not do so. The conclusion obtained is that The New York Times represents the issue in a neutral way, while Al-Jazeera is identified bias with those who oppose Trump's decision.